2017
DOI: 10.1007/s11999-016-4764-9
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Associated With Failure of Compressive Osseointegration Fixation?

Abstract: Background Compressive osseointegration is as an alternative to traditional intramedullary fixation. Two-to 10-year survivorship and modes of failure have been reported; however, as a result of relatively small numbers, these studies are limited in their ability to identify risk factors for failure. Questions/purposes (1) What is survivorship free from aseptic mechanical and survivorship free from overall failure of compressive osseointegration fixation? (2) What patient factors (age, sex, body mass index [BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 16 publications
(50 reference statements)
3
30
0
4
Order By: Relevance
“…Due to the nature of this retrospective review, we were unable to accurately assess or measure patients' adherence to weight-bearing recommendations, or to study differing weight-bearing restrictions in matched cohorts as would be ideal in a randomized controlled trial. Other modes of failure of compressive osseointegration fixation include periprosthetic fracture around a stable implant, infection, or progression of oncologic disease [4,23,27,28,31] , all of which are clinically relevant but outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the nature of this retrospective review, we were unable to accurately assess or measure patients' adherence to weight-bearing recommendations, or to study differing weight-bearing restrictions in matched cohorts as would be ideal in a randomized controlled trial. Other modes of failure of compressive osseointegration fixation include periprosthetic fracture around a stable implant, infection, or progression of oncologic disease [4,23,27,28,31] , all of which are clinically relevant but outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that risk of overall failure of proximal tibia and distal femur reconstructions was increased compared to the proximal femur with the Compress® device [27] .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Zum Impaction Grafting beim proximalen Femurersatz liegen nach aktuellem Kenntnisstand keine wegweisenden Studien vor. [20,21]. Klinisch konnte gezeigt werden, dass durch das Compress-System Überlebensraten der Femurfixation von 88 % nach 5 Jahren erzielt werden können.…”
Section: Anforderungen An Den Modularen Proximalen Femurersatzunclassified